Microscopic Features, Chromatographic Fingerprints and Antioxidant Property of Some Unconventional Green Leafy Vegetables Consumed in Bandundu, DR Congo - Bahati, Lydia Mangala; Kapepula, Paulin Mutwale; Kabamba, Nadège Ngombe; Moni, Bénédicte; Kafuti, Gisèle Makengo; Mungitshi, Patricia Mbombo; Pambu, Aaron; Bongo, Gedeon; Mukuta, Adam Tujibikila; Kabengele, Jimmy Kabeya; Mutunda, Clement Mbadiko; Frederich, Michel; et al. (Pharmacognosy Communications)
Introduction: Nutrition is an important aspect of public health because it is linked to many significant diseases and health problems. This work is part of the promotion of traditional foods from the Democratic Republic of Con- go, particularly in the province of Bandundu, by assessing the antioxidant capacity of 4 unconventional green leafy vegetables and determining their microscopic features and their chromatographic fingerprints. Materials and Methods: Methanolic extracts from leaves of traditional vegetables were characterized for their chemical fingerprint by TLC, HPLC-DAD and their in vitro antioxidant activities using ABTS, DPPH assays. Results: The microscopic analysis of the powder of leaves showed that each species presents characteristic elements allowing their distinction. Phytochemical screening revealed the presence of flavonoids, terpenes, steroids and qui- nones in all species. However, Entada gigas and Psophocarpus scandens also contain alkaloids, Salacia pynaertii and Tetrochirdium congolenses also contain anthocyanins. All extracts displayed a good radical-scavenging activity at the concentration range 1 – 60 µg/mL in the following order: S. pynaertii > T. congolense > E. gigas > P. scandens. S. pynaretii and T. congolense extracts showed significant antioxidant activity compared to quercetin, and this activity may depend on a synergic effect of several polyphenolic compounds. Conclusion: The high nutritive value of these traditional vegetables associated with their important antioxidant activities could contribute to diversifying diets for increased antioxidant consump- tion for Bandundu’s population, and could provide benefits for protection against oxidative damage under different conditions including konzo.
Keywords: Entada gigas; Konzo; Psophocarpus scandens; Salacia pynaer- tii; Tetrorchidium congolense; Traditional vegetable